THE EFFECT OF THE APPLICATION OF BIO-SOIL SOIL DESTRUCTION (NOVELGRO TERRA) AND THE REDUCTION OF THE AMOUNT OF NPK FERTILIZER DELIVERY ON THE GROWTH AND YIELD OF GREEN OKRA PLANTS (Abelmoschus esculentus. L) - Nindya Febri Setyo Utami (AGRONISMA, 2021)
Okra plant(Abelmoschus esculentus)is not widely known among the people of Indonesia. However, as the increasingly modern era of agricultural land in Indonesia has experienced a decrease in productivity on a large scale caused by the use of inorganic fertilizers and the use of pesticides that are not in accordance with the rules. Soil soil repair can improve the fertility rate of the soil so as to support plant growth and plant productivity. This study aims to find out the effect of soil soil application on the growth and yield of okra plants. and to find out the effect of soil soil application on reducing the amount of inorganic fertilizer use on the growth and yield of okra plants. The study used Group RandomIzed Design (RAK) with 10 treatments and 3 repeats. The results showed that the treatment of O9 (Without fertilizer NPK + Soil Soil Destruction) is the best treatment in growth, and at the result of productivity of tons/ha O9 treatment (Without fertilizer NPK + soil soil soil destruction) is the highest value on the parameters of productivity of tons/ha. These results mean that the application of soil soil destruction can replace NPK fertilizer.